The adolescent drug-crime relationship: desistence and gateway theories across user levels - Whiteford, Scott W. (Criminal justice recent scholarship, 2007)
Introduction -- Treacherous measurements -- Studying drugs and crime -- Conducting a study -- Adolescent substance use clusters -- Examining substance use clusters -- Adolescent substance use and crime -- Clusters versus traditional measure -- Research implications -- Appendices a-j: -- References